2020
DOI: 10.1111/cts.12770
|View full text |Cite
|
Sign up to set email alerts
|

Potential Protective Effects of the Water‐Soluble Chinese Propolis on Hypertension Induced by High‐Salt Intake

Abstract: High-salt (HS) intake is closely associated with the ignition and progression of hypertension. The mechanisms might be involved in endothelial dysfunction, nitric oxide deficiency, oxidative stress, and proinflammatory cytokines. Propolis is widely used as a natural antioxidant and is a well-known functional food for its biological activities, which includes antiinflammation, antimicrobial, and liver detoxification. In this study, we successfully replicated a HS diet-induced hypertensive rat model. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
10
0
3
Order By: Relevance
“…Hypertension and cardiovascular disease are considered relevant comorbidities for COVID-19 [ [125] , [126] , [127] ]. Propolis has demonstrated anti-hypertensive effects in rat models [ 33 , 34 , 128 , 129 ]. In Cameroon, it is used in popular medicine to treat various ailments, including high blood pressure [ 130 ].…”
Section: Comorbidities and Evidence Of How Propolis Can Help Reduce Tmentioning
confidence: 99%
“…Hypertension and cardiovascular disease are considered relevant comorbidities for COVID-19 [ [125] , [126] , [127] ]. Propolis has demonstrated anti-hypertensive effects in rat models [ 33 , 34 , 128 , 129 ]. In Cameroon, it is used in popular medicine to treat various ailments, including high blood pressure [ 130 ].…”
Section: Comorbidities and Evidence Of How Propolis Can Help Reduce Tmentioning
confidence: 99%
“…In high-salt intake hypertensive rats, Chinese propolis reduced the BP by reducing oxidative stress via a decrease in NOX expression. The consequent increase in endothelial NO bioavailability, together with an anti-inflammatory action (reduction of TNF-α and interleukin (IL)-6 levels) and with an improvement of the myocardial contractile function, ameliorated hypertension in this model [ 97 ].…”
Section: Cardiovascular Effects Of Propolismentioning
confidence: 99%
“…High-NaCl diet-induced hypertension has also been shown to be ameliorated by propolis. Zhou et al (2020) demonstrated that water-soluble propolis extract reduced the severity of hypertension induced by a high-NaCl diet in rats [88]. They demonstrated that the protective effect of a water-soluble extract of propolis was through several modes of action, such as the upregulation of antioxidant enzyme catalase (CAT) activity and the reduction in the vascular ROS level.…”
Section: Hypertensionmentioning
confidence: 99%
“…They demonstrated that the protective effect of a water-soluble extract of propolis was through several modes of action, such as the upregulation of antioxidant enzyme catalase (CAT) activity and the reduction in the vascular ROS level. Propolis also reduced inflammatory markers, such as TNF-α and IL-6, and improved endothelial function [88]. Furthermore, Mulyati et al (2021) investigated the antihypertensive effect of propolis collected from three different regions in Indonesia, namely, Riau Archipelago, Lampung, and South Sulawesi in NaCl-induced hypertensive rats.…”
Section: Hypertensionmentioning
confidence: 99%